Analysis of the Influence of Tiktok Content Type on Memories Coffee Purchase Decisions in Generation Z with Engagement Rate Moderation - Tampubolon, Alpian; Saputra, Bobby W. (Riviera Publishing, 2025)
This study aims to examine the influence of various TikTok content types on the purchase decision of Kopi Kenangan among Generation Z consumers, with engagement rate serving as a moderating variable. As one of the most dominant social media platforms among Gen Z, TikTok offers unique marketing opportunities through short-form, interactive, and viral content. Employing a quantitative and causal research design, this study collected data from 167 Gen Z respondents in Jabodetabek who have been exposed to Kopi Kenangan's TikTok content. The content types examined include product reviews, challenges & hashtags, storytelling & brand awareness, and promotional content. Purchase decisions were measured using indicators such as buying intention, brand preference, recommendation, actual purchase, and post-purchase satisfaction. Data were analyzed using PLS-SEM with a two-stage moderation approach. Findings reveal that all four types of TikTok content positively influence purchase decisions, with product reviews exerting the strongest impact. Furthermore, engagement rate significantly moderates the relationship between specific content types and purchase decisions. The study offers valuable insights for F&B digital marketers in crafting TikTok content strategies that are both engaging and conversion-driven.